PENYELESAIAN WANPRESTASI DALAM PERJANJIAN HUTANG PIUTANG DENGAN JAMINAN HAK TANGGUNGAN - DIAN SISCAWATI SETYAWAN (Fakultas Hukum Universitas Narotama, 2023)
Mortgage is one type of security right besides Mortgage, Pledge and Fiduciary. The guarantee right is intended to guarantee the debt of a debtor which gives the main right to a certain creditor, namely the holder of the guarantee right, to take precedence over other creditors if the debtor defaults. This study focuses on the mechanism for settling bad loans with mortgage guarantees and the execution procedure for mortgage guarantees in cases of default in debt agreements with mortgage guarantees. The problem approach in completing this research is by using the nature of the research in a descriptive analysis, namely by describing the analysis of the executorial power of mortgage rights in the event of bad credit (default) in the debt agreement submitted by the debtor in case Number 24 / Pdt.G / 2012 / PN.Pkl . Keywords: Mortgage, guarantee right, debt agreements, creditors